If institutional performance matters: Development comparisons of Lithuania, Latvia and Estonia - Tvaronavičienė, Manuela; Grybaitė, Virginija; Tvaronavičienė, Agnė (Journal of Business Economics and Management, 2009)
Presented paper aims to estimate and compare sustainable development processes in Lithuania, Latvia and Estonia after the European Union accession. Data embracing the 2004–2008 period is being analysed. Authors take into account that different approaches to countries’ development assessment might affect their comparison results. In order to obtain a multi‐faceted view, several variants of sustainable development estimations of Lithuania, Latvia and Estonia are being performed. Each variant represents a different approach to development perception. The difference lies in emphasis, which is being put on economic and institutional aspects of development. Juxtaposition of development estimation variants is expected to reveal range, within which the resulting index fluctuates and impacts ranging of countries. Integrated complex countries’ development index is computed by using multi‐criteria method. Authors of the paper compose a system of indicators, which is being employed for research purposes. Corollaries of investigation let us judge how much Lithuanian, Latvian and Estonian ranking according to estimated development level differs due to variations of approaches applied, and how sensitive calculations are to institutional performance and current economic downturn. First Publish Online: 14 Oct 2010